TRADISI RAWAH AMPING DI DESA JIRAK KABUPATEN SAMBAS TAHUN 2002-2023: Dari Ungkapan Rasa Syukur Hingga Menjadi Event Budaya - Nuridayanti, Kiki (Borneo : Journal of Islamic Studies, 2023)
The rawah amping tradition, a cultural gem of Jirak Village, is now in risk of being lost. Nevertheless, the rawah amping tradition was successfully revived due to the diligent efforts of the community and the Village Government. The objective of this study is to ascertain the evolution of the rawah amping custom in Jirak Village from 2002 to 2023. The research methodology used is the historical research technique, including four distinct stages: heuristics, verification, interpretation, and historiography. The main sources for study consist of village authorities, committees, and practitioners of the rawah amping tradition. Secondary sources include books, journals, online newspapers, and other pertinent materials. The research findings indicate that the evolution of the rawah amping tradition in Jirak Village can be categorized into two distinct phases. The initial phase, spanning from 2002 to 2010, is characterized by a decline in the practice of rawah amping, which involved modest and limited-scale expressions of gratitude following the rice harvest. During the period of 2011-2023, the rawah amping tradition underwent a systematic and planned process of strengthening and reaffirmation, ultimately transforming into a festive celebration known as the amping party. In addition to serving as a means of expressing thanks, the practice of this ritual has evolved into a cultural spectacle.